Studi Literatur Manajemen Perikanan Pada Situasi Bencana Covid-19 - Kurniawati, Dwi Shinta; Yulianto, Gatot; Munawir, Abdillah (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2024)
The Coivd-19 pandemic disaster has had a negative impact on the fisheries industry. The aims of this paper was to analyze the root causes, impacts and strategies dor sustainability fisherises management after the Covid-19 pandemic. The research method was carried out using the literature study. Analysis of the disscusion was carried out descriprively. The root of problem of hampering the fisheries industry was generally identified as 3 things, social, travel and trade restriction. The derivatives of these three root problems will certainly have an impact on the logistics system, distribution, price fluctuations, supply and demand, marketing system and the vulnerability of the people’s lives. Based on tragedy of the Covid-19, fisheries industry always needs to implement risk management, especially disaster risk mitigation to reduce impacts